Women in the Duma: Why Post-Soviet Russia Has Low Female Representation? A view from India - N. Kapoor (Сравнительная политика)
Quarter of a century after the disintegration of the Soviet Union, the Russian Duma, lower house of Parliament, still has a low representation of women. The article seeks to examine the causes for this phenomenon. It examines the factors that have been found to be responsible for the gender gap in parliaments across the world. It will then present this evidence in the light of the Russian experience to understand what lies behind the low level of representation of women in Russian national parliament. A mix of political, socio-economic and cultural factors will be analysed in detail to fi nd the causative aspects, analysing the inter-linkages between these various factors in play.